2016
DOI: 10.1038/srep37335
|View full text |Cite
|
Sign up to set email alerts
|

In-situ catalyzation approach for enhancing the hydrogenation/dehydrogenation kinetics of MgH2 powders with Ni particles

Abstract: One practical solution for utilizing hydrogen in vehicles with proton-exchange fuel cells membranes is storing hydrogen in metal hydrides nanocrystalline powders. According to its high hydrogen capacity and low cost of production, magnesium hydride (MgH2) is a desired hydrogen storage system. Its slow hydrogenation/dehydrogenation kinetics and high thermal stability are the major barriers restricting its usage in real applications. Amongst the several methods used for enhancing the kinetics behaviors of MgH2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The authors claimed that this fast kinetic behavior was attributed to the formation of a homogeneous nanocomposite system, in which nano-powders were adhered to all MgH 2 powders without exception. 83 The synthesized nanocomposite was able to perform 100 continuous cycle-life times of hydrogen charging/discharging at 275 C within 56 h without failure or degradation, as elucidated in Fig. 7c.…”
Section: Research Activities Devoted To Enhancing the Hydrogen Storagmentioning
confidence: 90%
See 2 more Smart Citations
“…The authors claimed that this fast kinetic behavior was attributed to the formation of a homogeneous nanocomposite system, in which nano-powders were adhered to all MgH 2 powders without exception. 83 The synthesized nanocomposite was able to perform 100 continuous cycle-life times of hydrogen charging/discharging at 275 C within 56 h without failure or degradation, as elucidated in Fig. 7c.…”
Section: Research Activities Devoted To Enhancing the Hydrogen Storagmentioning
confidence: 90%
“…6k and l. MgH 2 /5.5 wt% Ni nanocomposite powders obtained aer a short RBM time (25 h) revealed low values for the decomposition temperature (218 C), at which the apparent activation energy (E a ) was 75 kJ mol À1 . 83 In addition, the hydrogenation (Fig. 7a)/dehydrogenation (Fig.…”
Section: Research Activities Devoted To Enhancing the Hydrogen Storagmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts have been done to improve the hydriding and dehydriding properties such as element substitution (metal or metal oxides) as catalyst in nanometer scale and modification of ball milling technique have been used to improve sorption and kinetics properties [2][3][4]. Recently, the reactive ball milling under hydrogen atmosphere was successfully introduced to prepare hydrogen storage materials [5][6][7][8]. Here, we report on MgH2 catalyzed with small amount of Ni in nanoparticles scale and the preparation was done by reactive ball milling under 10 bar hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Eskandarany et al 7 have showed a new approach for catalyzing MgH2 with nano-Ni by high energy reactive ball milling under 50 bar of hydrogen atmosphere. They found that the sorption kinetics was examined at 275 °C within 8 minutes and produced ~5 wt.% H2 for 25 h of milling time.…”
Section: Introductionmentioning
confidence: 99%